Enhancement of Liver Toxicity on Diabetes Mellitus by a Universal Chemical Pollutant (Acrylonitrile) in Rats: Acrylonitrile Liver Toxicity in STZ Diabetic Rats - Sameer E. Alharthi (Journal of King Abdulaziz University: Medical Sciences, 2019)
The present study was designed to investigate potential liver damage due to acrylonitrile in Streptozotocin induced diabetes in rats. Twenty-four rats were divided into 4 treatment groups. Nondiabetic control rat receiving distilled water, non-diabetic rat receiving acrylonitrile aqueous solution (10 mg/kg/day), diabetic control rat receiving distilled water and diabetic rat receiving acrylonitrile aqueous solution. All groups received the treatment for 4 weeks. The animals were assessed for hepatoxicity markers in serum, oxidative stress markers, CYP2E1 activity and cyanide formation in tissues. Acrylonitrile significantly elevated serum aminotransferase, alanine aminotransferase, total bilirubin levels, triglycerides and total cholesterol in diabetic groups as compared to normal control group. Antioxidant markers like glutathione showed significant decline while a significant increase in malondialdehyde, superoxide dismutase and catalase in diabetic rats treated with acrylonitrile. CYP2E1 activity was observed in acrylonitrile – exposed nondiabetic and diabetic groups as compared to control. Cyanide formation was raised in both the nondiabetic and diabetic groups as compared to control group. Acrylonitriles can produce acute hepatic injury, induction of diabetes mellitus type II, and accomplish the CYP2E1 enzyme which sequentially leads to generation of oxidative stress and its metabolic product–cyanide that may potentiate the oxidative stress posing more deleterious effect.